PERLUNYA PENERAPAN SISTEM AKUNTANSI PADA USAHA KECIL MENENGAH - Puji Astuti, Dewi Saptantinah (Universitas Slamet Riyadi, 2010)
Abstract System is very important in the business activity, especially in business activity which very more transaction and complex. System devided in more procedur. Finally, the financial statement is compatible accounting standard. Therefore, need internal control system (ICS), organization which have good ICS, mistake could be minimalized. This research is descriptif and this object is an car accesories â€œGoro Profesionalâ€ in Surakarta. This research was aim to description for all businessman and everyone which need accounting systems in the business organization and make the financial statement is compatible accounting standard. The problema in this research is know what accounting systems used to in the business enterprises will be controlable and mistake can be minimalized. Result in this study is there are some mistake in this organization, beside there are some good practice in this organization, therefore this research try to search some solution in the problemain this organization and help to give for example financial statement which compatible accounting standard. Â Keywords: System, Procedur, Accounting System, Internal Control Systems